Amorphization of carbon nanotubes in water by electron beam radiation. (January 2020) - Barsotti, Elizabeth; Tan, Sugata P.; Goual, Lamia; Piri, Mohammad
Abstract: It is commonly assumed that carbon nanotubes (CNT's) are chemically stable in aqueous environments. Consequently, there has been significant interest in using them in applications where water is abundant, including agricultural fertilization, oil spill remediation, water treatment, food processing, and medicine. Indeed, despite outstanding questions regarding their toxicity, CNT's are already being employed commercially in some of these fields. Here, we use environmental transmission electron microscopy to show that when CNT's are subjected to electron beam radiation in the presence of water, amorphous carbon nanospheres, films, and globules can be synthesized. The type of amorphous carbon synthesized depends upon the surface functionality of the CNT's and the amount of water present. Nanospheres are formed in smaller amounts of water from unmodified CNT's, while amorphous films and globules form in large amounts of water from unmodified, polyethylene-glycol-functionalized, and carboxylic-acid-functionalized CNT's. Changes to the size, shape, and electron orbital hybridization of the CNT's due to amorphization increase their risk of toxicity to humans and the environment in applications, including all of those mentioned earlier, where CNT's are being employed alongside ionizing radiation. Our discovery of these amorphous transformations marks the first sub-atomic-resolution environmental observations of CNT's in water. Graphical abstract: Image 1